2023
DOI: 10.3390/pr11082272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Capsaicinoid Extraction Conditions from Mexican Capsicum chinense Var. Mayapan with Supercritical Fluid Extraction (SFE)

Abstract: Capsaicin (Cp) is a secondary metabolite produced by the Capsicum plant family. This molecule exhibits various biological properties such as antioxidant capacities, anti-obesogenic effects, and antidiabetic properties, among others. However, conventional extraction methods for Cp present several disadvantages including toxicity, extraction time, and low purity. Therefore, the utilization of supercritical fluid extraction techniques represents a viable option for obtaining highly pure and low-toxicity oleoresin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…Regarding the bioactive compound profile in the extract (Table 3), as expected, in all cases, the extract obtained showed a higher concentration of capsaicin than dihydrocapsaicin; this corresponds to what was reported for the genus C. chinense [17]. Aviles-Betanzos et al [45] reported the highest concentration of capsaicin (37.9 ± 0.84 g kg −1 extract) and dihydrocapsaicin (10.17 ± 0.18 g kg −1 extract) using SFEC at 45 • C, ≈100 bar, and 60 min. The results of capsaicinoids and carotenoids for the evaluated materials are similar to or higher than those found in the literature, which can be explained by the differences in capsicum varieties, maturate stage, or cultivation regions [19].…”
Section: Bioactive Compound Of Red Habanero Chili Pepper Extract From...supporting
confidence: 84%
“…Regarding the bioactive compound profile in the extract (Table 3), as expected, in all cases, the extract obtained showed a higher concentration of capsaicin than dihydrocapsaicin; this corresponds to what was reported for the genus C. chinense [17]. Aviles-Betanzos et al [45] reported the highest concentration of capsaicin (37.9 ± 0.84 g kg −1 extract) and dihydrocapsaicin (10.17 ± 0.18 g kg −1 extract) using SFEC at 45 • C, ≈100 bar, and 60 min. The results of capsaicinoids and carotenoids for the evaluated materials are similar to or higher than those found in the literature, which can be explained by the differences in capsicum varieties, maturate stage, or cultivation regions [19].…”
Section: Bioactive Compound Of Red Habanero Chili Pepper Extract From...supporting
confidence: 84%
“…Over the past 50 years, non-conventional methods have been developed that are more ecological and eco-friendly due to shorter operation time, less use of synthetic and organic chemicals, and better yield and quality of the extract. To increase the overall yield and selectivity of bioactive constituents from plant materials, ultrasound [76], pulsed electric field [77], microwave heating [78], enzymatic digestion [79], ohmic heating, supercritical fluids [80,81] and accelerated solvents (Wasilewski) have been investigated as unconventional methods.…”
Section: Discussionmentioning
confidence: 99%